TINJAUAN YURIDIS TERHADAP IMPLEMENTASI PERATURAN DAERAH NOMOR 16 TAHUN 2002 TENTANG PENERTIBAN ANAK-ANAK JALANAN DAN PENGEMIS DI KOTA SAMARINDA - Herlina Dwi Arini (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACT Background contained in this thesis is a rampant problem of street children and beggars in the city of Samarinda, the attention to this issue has a lot of good ideas poured out in the form of discussions and seminars which have been tried to be implemented by local government agencies and organizations or volunteers who are closely related to this issue. Basically the welfare of the child is not the same, depending on the level of welfare of their Parents. We can see in our country are still many children who live in slums, and one must struggle to make a living to support the family needs. Poverty, poor education, dysfunctional families and social environment also affects the life and growth of a child.The problems raised in this paper try is to shape how local government responsibility for street children and beggars in the city of Samarinda in terms of Bylaw No. 16 of 2002 and what are the efforts made by the local government in dealing with street children and beggars in Samarinda city.These problems, the Government began running Regulation 16/2002, but from the implementation of the law faced so many obstacles there are several explanations why the Government can not solve this problem optimally, this is due to the lack of attention to the children so that state they are utilized by the individuals to be empowered as street children and beggars.